Balancing Innovation and Tradition To Create Learning Opportunities for All Learners - Cox, Charlotte ([S.l.] : Distributed by ERIC Clearinghouse, 1997)
In an effort to improve instruction and give greater attention to teaching techniques that accommodate different learning styles, Nevada's Truckee Meadows Community College (TMCC) implemented the 4MAT System Fundamental Training for faculty. The 4MAT System identifies four major learning styles (i.e., learners who are primarily interested in personal meaning, those interested in facts, those interested in how things work, and those interested in self-discovery) and recommends that learners be taught in all four styles. The System is designed to move learners through an eight-step natural cycle of learning, in which students experience a problem-solving activity before receiving instruction, students reflect on that experience, the concept to be taught is introduced in relation to students' personal experience, instruction is provided on the concept, hands-on activities are provided for practice, students experiment with related ideas, feedback is provided, and students share with others. As a result of the 4MAT training, the college has witnessed increased networking among faculty, while faculty report a newfound enthusiasm for teaching and successes with students. There are also certified 4MAT system trainers on campus, allowing the college to offer the techniques to staff and community members indefinitely. (TGI)
ERIC Note: In: Walking the Tightrope: The Balance between Innovation and Leadership. Proceedings of the Annual International Conference of the Chair Academy (6th, Reno, NV, February 12-15, 1997); see JC 970 185.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Cognitive Style; Community Colleges; Faculty Development; Inservice Teacher Education; Instructional Effectiveness; Instructional Improvement; Learning Strategies; Learning Theories; Teacher Effectiveness; Teaching Methods; Two Year Colleges; 4MAT System; Reports, Descriptive; Speeches/Meeting Papers